2014
DOI: 10.1016/j.ptsp.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tackling on shoulder joint positioning sense in semi-professional rugby players

Abstract: Results: Prior to the tackling task, joint positioning sense was poorer at the 45° criterion angle than for 20° off the athletes' maximal range angle. Following the tackling task, error scores were significantly increased from baseline measures at the outer range criterion angle for both dominant and non-dominant sides. In contrast to previous research the detrimental effect of the task was also greater. In addition, there was a significant decrease in accuracy at the 45 ° criterion angle for the players' nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Attention should be targeted to train the neuromuscular control that is required for the player to adopt the optimal tackling position [15]. This particularly involves the glenohumeral and scapulathoracic dynamic neuromuscular control that is required to achieve the ideal shoulder position for the tackle [22]. The integrity of the glenohumeral joint and its capsuloligamentous support is under maximum strain when the joint is under load at the end of its range of motion [18].…”
Section: Discussion ▼mentioning
confidence: 99%
“…Attention should be targeted to train the neuromuscular control that is required for the player to adopt the optimal tackling position [15]. This particularly involves the glenohumeral and scapulathoracic dynamic neuromuscular control that is required to achieve the ideal shoulder position for the tackle [22]. The integrity of the glenohumeral joint and its capsuloligamentous support is under maximum strain when the joint is under load at the end of its range of motion [18].…”
Section: Discussion ▼mentioning
confidence: 99%
“…103 117 For example, Seminati et al reported a 13% higher impact force from the dominant shoulder. 132 Players seem to have poorer shoulder positional sense of their non-dominant shoulder while tackling 133 and adopt a more passive biomechanical strategy to generate the drive needed to stop a ball carrier. 132 As such, tackles on the dominant shoulder produce higher impact forces on contact, whereas the non-dominant shoulder produces force over longer durations.…”
Section: Injury Risk Factors and Performance Determinantsmentioning
confidence: 99%
“…Numerous position-specific factors affect the likelihood of such an injury. Players sustaining an initial anterior instability event were more likely to injure their non-dominant shoulder, and this may be related to impaired coordinated muscle activation and joint position sense [2,22]. Locks and full backs were also found to be at a greater risk of re-injury and wings to be at decreased risk of re-injury of their shoulders.…”
Section: Conclusion ▼mentioning
confidence: 99%
“…The authors were unable to clarify if decreased activation was evidence for efficient recruitment or if increased activation was evidence for greater concentration and control. Morgan and Herrington [22] found that the non-dominant shoulder had significantly impaired joint position sense at the mid and outer ranges of external rotation after a dynamic tackling task. As this is the position in which the shoulder is most at risk of instability and also a position commonly encountered in tackling improved neuromuscular control of the non-dominant shoulder could reduce the number of anterior dislocations requiring Bankart repairs.…”
mentioning
confidence: 99%